2009
DOI: 10.1002/jcb.22086
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical force inhibits osteoclastogenic potential of human periodontal ligament fibroblasts through OPG production and ERK‐mediated signaling

Abstract: Periodontal ligament and gingival fibroblasts play important roles in bone remodeling. Periodontal ligament fibroblasts stimulate bone remodeling while gingival fibroblasts protect abnormal bone resorption. However, few studies had examined the differences in stimulation of osteoclast formation between the two fibroblast populations. The precise effect of mechanical forces on osteoclastogenesis of these populations is also unknown. This study revealed that more osteoclast-like cells were induced in the co-cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(59 citation statements)
references
References 32 publications
3
54
0
2
Order By: Relevance
“…The results of the current study indicate that various fibroblastic cells naturally produce OPG, thereby supporting the inhibitory roles of fibroblasts on osteoclastogenesis. There are also significant findings showing that mechanical force induces the production of both OPG and RANKL by PLF, while OPG is predominant over RANKL [Yamamoto et al, 2006;Nakajima et al, 2008;Kook et al, 2009]. Importantly, however, the results from GCF analysis showed that the levels of RANKL are naturally higher than those of OPG in this cell type.…”
Section: Discussionmentioning
confidence: 66%
“…The results of the current study indicate that various fibroblastic cells naturally produce OPG, thereby supporting the inhibitory roles of fibroblasts on osteoclastogenesis. There are also significant findings showing that mechanical force induces the production of both OPG and RANKL by PLF, while OPG is predominant over RANKL [Yamamoto et al, 2006;Nakajima et al, 2008;Kook et al, 2009]. Importantly, however, the results from GCF analysis showed that the levels of RANKL are naturally higher than those of OPG in this cell type.…”
Section: Discussionmentioning
confidence: 66%
“…Numerous studies have, however, pointed out that various types of cells, including endothelial cells, smooth muscle cells, osteoblasts, chondrocytes, and fibroblasts, appear to share common signaling pathways; nevertheless, the eventual response of a given cell type to mechanical load depends on mechanical loading conditions and the types of signaling molecules and transcription factors that are expressed [14]. In this study, ligamentum flavum fibroblasts were exposed to mechanical force by applying a well-established in vitro compression model of centrifugation of cultured cells [9,10]. The result demonstrated that viability of ligamentum flavum fibroblasts decreased in proportion to the centrifugal stress loaded, whereas no significant cellular death was noted.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were centrifuged at 500 and 1000 rpm/min for 10, 30, 60, and 90 min by horizontal microplate rotor (Eppendorf 5810R Centrifuge, Hamburg, Germany) under ambient conditions (temperaturecontrolled, but ambient room air) as previously described [9,10]. The paired -control of each tested condition was adjusted for each paired period ambient condition (temperature-controlled, but ambient room air) for 10, 30, 60, and 90 min.…”
Section: Application Of Mechanical Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcription factors of the NF-jB family are key players in the initiation of the inflammatory response, and NF-jB regulates inflammatory cytokines, including TNF-a and RANKL [29]. Many investigators have reported that signaling molecules, such as Rho kinase [30,31], focal adhesion kinase (FAK) [30], NF-jB [32,33], c-fos [34], mitogen-activated protein kinase (MAPK) [extracellular signal-regulated kinase (ERK), c-jun N-terminal kinase (JNK) and p38 MAPK] [35][36][37][38][39], and nitric oxide [40] are increased in PDL cells after mechanical stimulation. Furthermore, Copland and Post [41] found that stretch-induced HSP70 expression was mediated via NF-jB in fetal lung epithelial cells.…”
Section: Discussionmentioning
confidence: 99%